PERANCANGAN APPLIKASI BERGERAK TRASHSURE DENGAN DESIGN THINKING SEBAGAI SOLUSI PERMASALAHAN SAMPAH BERBASIS KOMUNITAS - Santoso, Halim Budi; Siang, Jong Jek; Soerjanto, Josephine Vania (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
Waste from meetings and gatherings is often just thrown away and collected by garbage collectors. This garbage has economic value for the surrounding community as an additional income. However, collecting this kind of garbage requires communication media that can help to connect the owners and the garbage collectors. To understand the underlying mechanisms in creating good communication media, this study utilizes a design thinking method to design TrashSure, a community-based mobile application without financial transactions and less profit-oriented. The TrashSure application was designed by analyzing the interview data of 10 people for each actor type: garbage collector and garbage owner. We received some feature recommendations to advance the communication channels, such as trash ownership and supporting data, such as time, type, volume, and location. In addition, the rating feature is essential to understand the credibility of the garbage collectors. Then, we evaluate the usability using the System Usability Scale (SUS) with ten respondents. The result shows a fairly good predicate with a score of 75.25.